کنزیومرازم کے مسلم معاشرے پر اثرات: اسلامی تعلیمات کی روشنی میں تحقیقی مطالعہ: Impact of Consumerism on Muslim Society and its Individuals: A Study in the light of Islamic Teachings (Al Basirah, 2023)
The consumer movement paradoxically emphasizes customer autonomy while acknowledging the drawbacks of excessive wealth pursuit and debt entanglement. This research deals with the impact of consumerism on individuals and society, framed within the context of Islamic teachings. Analyzing consumerist behaviors, the study explores their alignment with Islamic principles and their effects on the socio-economic landscape. The research contributes a nuanced perspective on the implications of consumerism, emphasizing its correlation with Islamic values. By examining key themes, such as individual behavior and societal consequences, the study sheds light on the intricate interplay between consumerism and Islamic teachings. This comprehensive analysis aims to deepen our understanding of these dynamics, offering valuable insights into navigating contemporary challenges while upholding Islamic values in the realm of consumption. Moreover, this study explores the concept, revealing that unchecked materialism can lead to more problems than benefits, causing mental and practical harm to the masses.
Keywords: Consumerism; Muslim Society; Materialism; Islamic Values; Socio-economic Landscape